BIOPORI: SOLUSI RAMAH LINGKUNGAN UNTUK MASYARAKAT DESA LIPUKASI - Najmah Mudiah; Anggi Maharani; Nursyelah Nursyelah; Marwah R; Diva Aprilya; Dewi Srinita Abbas Dewi Srinita Abbas (Media Literasi Indonesia, 2025)
Water and environmental management issues in rural areas remain a significant challenge that directly affects community well-being. One of the most common problems encountered is waterlogging caused by high rainfall and the limited availability of natural drainage systems.To address this issue, biopore technology has been implemented in Lipukasi Village, Tanete Rilau Sub-district, Barru Regency. This program was also designed to raise public awareness of the importance of water conservation and sustainable environmental management through the use of biopores. The implementation method employed a participatory approach, involving local residents directly in the construction of biopore infiltration holes at several strategic locations within the village. The activity focused not only on technical aspects but also emphasized education through training and community outreach. Evaluation results indicate that the application of biopore technology has had a positive impact, marked by improved soil absorption capacity, reduced water stagnation, and increased soil fertility due to natural composting processes occurring within the biopores.The success of this program demonstrates that biopore technology offers a practical and environmentally friendly solution for water management in rural areas.